L'herència del debat literari sobre la condició femenina en l'obra dramàtica de Francesc Palanca i Roca. - GARCIA GÁZQUEZ, HILARI (Scripta, 2020)
19th century researchers consider that 18th century drama genres, especially the «sainet» (a comic sketch), are a source of documentation on those years society. Consequently, we can follow the habits, uses and traditions of the Valencian people of that period through an important part of the drama production by Francesc Palanca i Roca (1834-1897), even the dispute or debate on women that used to flood the European literary and academic circles of the medieval age. In this respect, we will see how the drama plays by Palanca i Roca gather the heritage of misogynous topics and the arguments on women's condition defence, a heritage coming from the cultivated literature as well as from the popular one. All in all, the detection and identification of these elements will be the objective of the present work.